Communicating complexity: interactive model explorers and immersive visualizations as tools for local planning and community engagement - Robert Newell Robert.Newell@ufv.ca; Nate McCarthy; Ian Picketts; Fynn Davis; Grace Hovem; Stefan Navarrete (Canadian Science Publishing, 2021)
Models that capture relationships between a variety of social, economic, and environmental factors are useful tools for community planning; however, they are often complex and difficult for diverse audiences to understand. This creates challenges for participatory planning and community engagement. Conducted in the community of Squamish (British Columbia, Canada), this study develops and examines tools for communicating outcomes of a community scenario modelling exercise to diverse stakeholders. These tools are (i) a "model explorer" and (ii) realistic, immersive visualizations. The model explorer is an online, HTML5-based tool that can be used to learn about the model, view community scenario maps, and explore potential outcomes of the scenarios. The visualizations are virtual environments that are navigated from the first-person perspective, and they were developed using a combination of ArcGIS, Trimble SketchUp, Adobe Photoshop, and the Unity3D game engine. A local government and community stakeholder focus group and public open house event were held to solicit feedback on the scenarios and tools. Findings of the research suggest that the two types of tools can be used in a complementary fashion, and tool integration can better harness their respective strengths in a manner that comprehensively communicates the implications of different development pathways to diverse community members.